Discourse Markers in Peer Reviews of Academic Essays By Future Teachers of English as a Foreign Language - Kapranov, Oleksandr (Studia Anglica Posnaniensia, 2021)
This article presents and discusses a quantitative investigation of discourse markers (further – DMs) in the corpus of peer reviews of academic essays in didactics written by a group of future teachers of English as a Foreign Language (EFL). In total, 12 future EFL teachers at an intermediate level of EFL proficiency (henceforth – participants) took part in the study. The participants were instructed to form dyads and write peer reviews of each other’s academic essays on a range of topics in EFL didactics. Two corpora were used in the study, the corpus of the participants’ academic essays in EFL didactics and the corpus of peer reviews thereof. The corpora were analysed using WordSmith (Scott 2008) in order to establish the frequencies of the use of DMs per 1000 words. The results of the quantitative analysis of the corpora indicated that the participants employed a repertoire of stylistically neutral DMs in their peer reviews that was quantitatively similar to that of the academic essays. These findings will be further discussed in the article.